2021
DOI: 10.3390/toxins13120898
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthis Semen Suppresses Lipopolysaccharide-Induced Neuroinflammation by Regulating the NF-κB Signaling Pathway and HO-1 Expression in Microglia

Abstract: Neuroinflammation, which is mediated by microglia that release various inflammatory cytokines, is a typical feature of neurodegenerative diseases (NDDs), such as Alzheimer’s disease and Parkinson’s disease. Hence, alleviating neuroinflammation by downregulating pro-inflammatory action, and upregulating anti-inflammatory action of microglia is an efficient therapeutic target for NDDs. In this study, we evaluated whether trichosanthis semen (TS), a dried ripe seed of Trichosanthes kirilowii Maximowicz, reduces l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Nrf2 is a key factor in protecting cells from oxidative stress and inflammationinduced damage, which modulates the levels of antioxidants and detoxification enzymes, such as HO-1, superoxide dismutase 1, NAD(P)H dehydrogenase 1, and glutathione peroxidase 1 [33]. A recent study has shown that a dried ripe seed of Trichosanthes kirilowii Maximowicz, Trichosanthis semen, could inhibit LPS-induced inflammation in BV2 7 Oxidative Medicine and Cellular Longevity microglial cells through activating HO-1 and inhibiting NF-κB signaling [34]. Our findings reveal that THC treatment reduces nitrite production (Figure 2(e)).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a key factor in protecting cells from oxidative stress and inflammationinduced damage, which modulates the levels of antioxidants and detoxification enzymes, such as HO-1, superoxide dismutase 1, NAD(P)H dehydrogenase 1, and glutathione peroxidase 1 [33]. A recent study has shown that a dried ripe seed of Trichosanthes kirilowii Maximowicz, Trichosanthis semen, could inhibit LPS-induced inflammation in BV2 7 Oxidative Medicine and Cellular Longevity microglial cells through activating HO-1 and inhibiting NF-κB signaling [34]. Our findings reveal that THC treatment reduces nitrite production (Figure 2(e)).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharides have the ability to directly induce neuroinflammation and are frequently employed in constructing neuroinflammation models for numerous animal and cell culture experiments. Research has illustrated that lipopolysaccharide-induced neuroinflammation exerts its effects through the NF-κB pathway in cells such as microglia and neurons [130][131][132].…”
Section: Nf-κbmentioning
confidence: 99%
“…The activation of NRF2 leads to the expression of HO-1, and the upregulation of HO-1 expression decreased the release of proinflammatory cytokines such as TNF-α, IL-6, etc. 18 HO-1 converts heme into biliverdin and CO, which play an important role in cytoprotection against oxidative stress. 19 Low concentration of CO can attenuate NF-κB p65 nuclear translocation.…”
Section: The Role Of Nrf2 In Crcmentioning
confidence: 99%